Nontuberculous Mycobacteria and Heterologous Immunity to Tuberculosis - Shah, Javeed A (J Infect Dis, 2019)
Development of an improved tuberculosis (TB) vaccine is a high worldwide public health priority. Bacillus Calmette-Guerin (BCG), the only licensed TB vaccine, provides variable efficacy against adult pulmonary TB, but why this protection varies is unclear. Humans are regularly exposed to non-tuberculous mycobacteria (NTM) that live in soil and water reservoirs and vary in different geographic regions around the world. Immunologic cross-reactivity may explain disparate outcomes of BCG vaccination and susceptibility to TB disease. Evidence supporting this hypothesis is increasing but challenging to obtain due to a lack of reliable research tools. In this review, we describe the progress and bottlenecks in research on NTM epidemiology, immunology and heterologous immunity to Mtb. With ongoing efforts to develop new vaccines for TB, understanding the effect of NTM on vaccine efficacy may be a critical determinant of success.